EXPLORING JAPAN’S SOCIETY 5.0 : Identifying key factors shaping the development of Society 5.0 - Ota, Shiori (My University, 2021)
With the rapidly evolving digital landscape such as the emergence of artificial intelligence, the internet of things (IoT), and robotics, it is becoming ever more critical for countries to take effective and transformative measures to keep up with drastic changes brought by those emerging technologies. At the same time, the world is increasingly facing multiple societal challenges including rapid population ageing, climate change, natural disasters, and ever-growing concentration of wealth. To respond to such global trends, the government of Japan presented an ambitious vision, Society 5.0. It is about creating a human-centric society where both economic advancement and the resolution of various social issues are attained with the help of digital technologies. The objective of this thesis is to gain an in-depth understanding of Society 5.0 and examine the potential factors which may shape the human-centred society illustrated in Society 5.0. This thesis first conducted extensive and exploratory research about the background of Society 5.0. The selected method is qualitative research by interviewing experts who have or had an experience of being involved in a project or a creation process of Society 5.0. As a result, key findings and factors were produced. As a main conclusion from this research, first, it will be vital to create technological frameworks that are based on reliability, transparency and openness in order to realise the envisioned society through the use of emerging technologies. Second, demonstrating concrete examples is essential to prove the feasibility of the vision. Lastly, the inclusion and collaboration of multi-stakeholder is key in sharing and realising the common future vision and designing a society that can benefit all.
Keywords: Society 5.0, Future Studies, Industry 4.0, AI, Social Innovation